Котлован: повести - Платонов Андрей Платонович (Художественная литература, 1987)
Экземпляры: б/ф №12 (20190515) / Инвентарный номер: 12711 / Цена: 1.50 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 37 / ББК: 84(2Рос=Рус)6